Gut Microbiome and Liver Diseases - Shalimar (J Clin Exp Hepatol, 2014)
Nan Qin(1,2), Fengling Yang(1), Ang Li(1), Edi Prifti(3), Yanfei Chen(1), Li Shao(1,2), Jing Guo(1), Emmanuelle Le Chatelier(3), Jian Yao(1,2), Lingjiao Wu(1), Jiawei Zhou(1), Shujun Ni(1), Lin Liu(1), Nicolas Pons(3), Jean Michel Batto(3), Sean P. Kennedy(3), Pierre Leonard(3), Chunhui Yuan(1), Wenchao Ding(1), Yuanting Chen(1), Xinjun Hu(1), Beiwen Zheng(1,2), Guirong Qian(1), Wei Xu(1), S. Dusko Ehrlich(3,4), Shusen Zheng(2,5) and Lanjuan Li(1,2) Alterations of the human gut microbiome in liver cirrhosis. Nature. 2014 Jul 23 [Epub ahead of print]. (1)State Key Laboratory for Diagnosis and Treatment of Infectious Disease, The First Affiliated Hospital, College of Medicine, Zhejiang University, 310003 Hangzhou, China;(2)Collaborative Innovation Center for Diagnosis and Treatment of Infectious Diseases, Zhejiang University, 310003 Hangzhou, China;(3)Metagenopolis, Institut National de la Recherche Agronomique, 78350 Jouy en Josas, France;(4)King's College London, Centre for Host-Microbiome Interactions, Dental Institute Central Office, Guy's Hospital, London Bridge, London SE1 9RT, UK;(5)Key Laboratory of Combined Multi-organ Transplantation, Ministry of Public Health, the First Affiliated Hospital, Zhejiang University, 310003 Hangzhou, China.